Unveiling the hidden culprit: salinity inhibition on phosphorus recovery from high-salt wastewater via vivianite crystallization - Yi Cai; Yifan Du; Pin Zhao; Weilong Song; Xinhua Wang (Water Research, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Draw solution contamination undermines FO-MD stability for transfer station leachate treatment - Weilong Song; Mindi He; Yifei Xie; Boyan Xu; Pin Zhao; Xinhua Wang; Ng Yong (Water Research, 2026)

A comparative study of methods for quantifying sand-sized sediment grain textural parameters - Xiaotian Shen; Xing Jian; Wei Zhang; Ruolan Liao; Dongming Hong; Chao Li; Shaohua Zhao; James T. Liu; Yuan-Pin Chang (Sedimentary Geology, 2026)

Functional characterization of IRF2 and IRF2a in Japanese eel (Anguilla japonica) identifies dual pathways suppressing interferon responses - Haijun Qin; Dongli Li; Gejie Zhao; Pin Nie; Wenshu Huang; Bei Huang (Fish & Shellfish Immunology, 2026)

Cordycepin-mediated protection against bisphenol A–induced male reproductive toxicity via PI3K/mTOR/HIF-1α signaling - Wenjuan Yang; Jiang Guo; Zhaorui Shuai; Shuai Han; Xuguang Jing; Hui Long; Nan Li; Yanni Zhao; Pin Gong; Yuxi Guo (Food Research International, 2026)

Occurrence, distribution, and risk assessment of antibiotics in typical aquaculture environment of Southern Jiangsu, China - Zhen Kuang; Wenfeng Zheng; Weilong Song; Pin Zhao; Xinhua Wang (Journal of Environmental Sciences, 2026)

Sea buckthorn for future foods: bioactive mechanisms, synthetic biology, and precision delivery systems - Nan Li; Peidong Fan; Lulu Wang; Luole Feng; Hui Long; Wenjuan Yang; Jing Wang; Yanni Zhao; Huan Liu; Yuxi Guo; Pin Gong (Food Research International, 2026)

Immunomodulatory mechanism of Pleurotus eryngii polysaccharides in acrylamide-induced mice via the P2X7-NLRP3 pathway, metabolic homeostasis and gut microbiota - Jing Wang; Xiuxiu Liu; Dongliang Jin; Man Wang; Nan Zhang; Yanni Zhao; Wenjuan Yang; Nan Li; Xuefeng Chen; Pin Gong (Food Bioscience, 2026)

Numerical investigation of thermo-mechanical response and heat transfer in clay during thermal cone penetration testing - Jing Hu; Pin-Qiang Mo; Guo-Jun Cai; Zhao Lu; Abolfazl Eslami; Hai-Sui Yu (Computers and Geotechnics, 2026)

A CPTu-based method for evaluating consolidation characteristics of under-consolidated soils - Yu-cheng Li; Pin-Qiang Mo; Guojun Cai; Zhao Lu; Yan Zhuang; Hai-Sui Yu (Ocean Engineering, 2026)

Pyrolysis behaviors of lump sub-bituminous coal. Part 2: Effect of particle size - Zong-Pin Fu; Le-Le Qiu; Yi-Bin Huang; Yun-Peng Zhao; Jian Zhou; Jing Liang; Jian Xiao; Fang-Jing Liu (Fuel, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Long-term low-dose N, N-dimethylformamide exposure disturbs hepatic lipid and glucose homeostasis in mice - Shu-Jun Hong; Ming-Bao Zhang; Le-Yi Qi; Tian-Hao Zhao; Pin Wang; Tao Zeng (Toxicology, 2026)

Analysis of insertion/deletion variation of litter size in Guizhou black goat - Yang Yang; Yan Pin Zhao; Yong Han (Tropical Animal Health and Production, 2025)

Marine quorum quenching consortium for biofouling control in membrane bioreactor under salinity stress - Weilong Song; Chengyu Wan; Ziang Ding; Boyan Xu; Pin Zhao; Xinhua Wang; How Yong Ng (Water Research, 2025)

Electroactive biofilm enhances synergistic degradation of sulfamethoxazole and roxarsone in actual livestock wastewater: extracellular electron transfer drives metabolic network remodeling - Pin Peng; Xinyu Yan; Lixiang Chen; Xiang Li; Huiying Yang; Yijing Miao; Feng Zhao (Environmental Research, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Isolation of a highly virulent strain of Flavobacterium columnare Ci2323 and development of its live attenuated vaccine candidate in grass carp (Ctenopharyngodon idella) - Thusyakaanth Sivaranjan; Zhao Zhang; De Feng Zhang; Xiu Long Jiang; Shu Ya Zhang; Tian Tian He; Pin Nie; Hai Xia Xie (Aquaculture, 2025)

Multi-hazard fragility analysis of cross-sea cable-stayed bridges cable bent tower under seismic-wind combined action - Yan Liang; Yu-zhen Kong; Li Yan; Zheng-hao Zhao; Pin-wu Guan (Soil Dynamics and Earthquake Engineering, 2025)

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

The mafic–ultramafic roots of a magmatic arc from the East Kunlun Orogen, NW China - Zhi-Xiong Zhao; Guo-Chen Dong; M. Santosh; Di-Cheng Zhu; Hui-Lei Kong; Shu-Jun Lü; Pin-Yan Zhong (Gondwana Research, 2025)

Corrigendum to “N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater” [Chem. Eng. J. 491 (2024) 151763] - Pin Peng; Lixiang Chen; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Recent progress in optimization of RANS turbulence models for accurate urban airflow and contaminant dispersion simulations - Sumei Liu; Longhui Xu; Bingqian Chen; Zhipeng Deng; Pin Li; Runmin Zhao; Qingyan Chen (Sustainable Cities and Society, 2025)

Sacrificial reduction effects derived inorganic-rich hybrid solid electrolyte interfaces for long-term and high reversibility aqueous zinc-ion batteries - Yu Chen; Jiahong Fan; Qian Li; Pin Yi; Houfu Tu; Dedong Shan; Wentao Wang; Shulin Zhao; Yang Zhang; Yuping Wu; Yuhui Chen; Dengji Xiao (Chemical Engineering Journal, 2025)

Oligosaccharide-assisted resolution of holothurian fucosylated chondroitin sulfate for fine structure and P-selectin inhibition - Ying Pan; Huifang Sun; Xi Gu; Sujuan Li; Shengtao Yang; Liang Zhang; Hui Mao; Pin Wang; Shasha Yang; Ronghua Yin; Zhili Zuo; Jinhua Zhao (Carbohydrate Polymers, 2025)

A novel application of slow-release fertilizers in fertilizer-drawn forward osmosis for real domestic wastewater treatment - Chenchen Li; Pin Zhao; Zunaira Habib; Weilong Song; Xinhua Wang (Journal of Water Process Engineering, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Iron/nitrogen/sulfur co-doped cyanobacteria derived carbon composites for enhanced hydroxychloroquine degradation via primary nonradical pathway in peroxymonosulfate-based fenton-like system - Tao Wang; Yuxuan Yang; Zheren Tang; Pin Zhao; Kunlun Yang; Xinhua Xu (Journal of Cleaner Production, 2025)

Unlocking anaerobic digestion potential via extracellular electron transfer by exogenous materials: Current status and perspectives - Xinyu Yan; Pin Peng; Xiang Li; Xudong Zhou; Lixiang Chen; Feng Zhao (Bioresource Technology, 2025)

Enhancing degradation of antibiotic-combined pollutants by a hybrid system containing advanced oxidation and microbial treatment, a review - Pin Peng; Xinyu Yan; Xudong Zhou; Lixiang Chen; Xiang Li; Yijing Miao; Feng Zhao (Journal of Hazardous Materials, 2024)

Astragaloside IV alleviates diabetic nephropathy by modulating the gut-kidney axis and AMPK/PI3K/AKT pathway - Pin Gong; Hui Long; Qian Yang; Rui Zhou; Wenjuan Yang; Fuxin Chen; Jianwu Xie; Yanni Zhao; Hongbo Xu (Food Bioscience, 2024)

On-device charge engineering in 2D perovskite oxides for high performance photodetectors - Yong Zhang; Lin Wang; Xiujun Wang; Xiaohang Pan; Pin Zhao; Ye Liu; Qing Guo; Lixing Kang; Xiaosheng Fang (Chemical Engineering Journal, 2024)

New insights into biofouling worsening induced by salinity stress in membrane bioreactor: Response of quorum sensing system and its regulation role - Weilong Song; Huaning Wu; Enyu Liu; Boyan Xu; Pin Zhao; Xinhua Wang; How Yong Ng (Chemical Engineering Journal, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Structural characterization and hypoglycemic activity of Cordyceps sinensis polysaccharide (CSP-3) - Pin Gong; Yingying Ke; Xiaojuan Wang; Hui Long; Wenjuan Yang; Jing Wang; Nan Li; Yanni Zhao; Fuxin Chen; Yuxi Guo (Food Bioscience, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Structurally tuned polyamide membranes via the polyvinylpyrrolidone-modulated interfacial polymerization reaction for enhanced forward osmosis performance - Yao Jiang; Pin Zhao; Subo Xu; Hao Liu; Wenyan Zhang; Weilong Song; Xinhua Wang (Desalination, 2024)

Research on the Power Output of Different Floating Wind Farms Considering the Wake Effect - Jiaping Cui; Xianyou Wu; Pin Lyu; Tong Zhao; Quankun Li; Ruixian Ma; Yingming Liu (Journal of Marine Science and Engineering, 2024)
For floating wind turbines, one of the most interesting and challenging issues is that the movement of the rotor is strongly related to its floating platform, which results in corresponding variations in the wake characteristics of the turbine. Because the aerodynamic efficiency of the downstream turbines is affected by the wake characteristics, the power output will consequently vary depending on the different types of floating wind turbines and floating wind farms used. In this study, the rotor movement, wake characteristics, and corresponding wind farm power output are analyzed using a numerical method for three typical floating wind turbines: the semisubmersible type, spar buoy type, and tension leg platform type with a 5 MW configuration. A fixed-bottom monopile wind turbine is adopted as a benchmark. The simulation results show that of the three floating wind turbines, the rotor position and wake center are most dispersed in the case of the spar buoy type, and its wake also has the lowest impact on downstream wind turbines. Additionally, the power output of the corresponding spar buoy type wind farm is also the highest at different wind speeds, followed by the semisubmersible type, tension leg platform type, and then the fixed-bottom type. In particular, at low wind speeds, the wake effects differ significantly among the various types of wind turbines.

Experimental research on pull-out behavior of steel-UHPC composite beams with new composite dowels connectors - Pin Zhao; Xudong Shao; Junhui Cao; Xueliang Rong (Engineering Structures, 2024)

N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater - Pin Peng; Lixiang Chen.; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2024)

Fulvic acid-mediated efficient anaerobic digestion for kitchen wastewater: Electrochemical and biochemical mechanisms - Xinyu Yan; Pin Peng; Xudong Zhou; Xiang Li; Lixiang Chen; Feng Zhao (Water Research, 2024)

New insights on destruction mechanisms of waste activated sludge during simultaneous thickening and digestion process via forward osmosis membrane - Xiawen Yi; Zhiwei Wang; Pin Zhao; Weilong Song; Xinhua Wang (Water Research, 2024)

Anaerobic acidification membrane bioreactor operating at acidic condition for treating concentrated municipal wastewater: Performance and implication - Huihui Zhong; Qiming Wang; Mengfei Wu; Pin Zhao; Weilong Song; Xinhua Wang (Bioresource Technology, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Dual role of birnessite on the modulation of acid production and reinforcement of interspecific electron transfer in anaerobic digestion - Xinyu Yan; Lixiang Chen; Pin Peng; Fan Yang; Liping Dai; Han Zhang; Feng Zhao (Science of The Total Environment, 2024)

V-ATPase E mediates Cry2Ab binding and toxicity in Helicoverpa armigera - Yuge Zhao; Pin Li; Xue Yao; Yuepu Li; Yu Tian; Guiying Xie; Zhongyuan Deng; Shuxia Xu; Jizhen Wei; Xianchun Li; Shiheng An (Pesticide Biochemistry and Physiology, 2024)

Synergistic defect and doping engineering building strong bonded S-scheme heterojunction for photocatalysis - Jia-Jing Zhang; Jun Di; Yun-Peng Zhao; He-Shan Zheng; Pin Song; Jing-Zhi Tian; Wei Jiang; Yong-Jie Zheng (Chemosphere, 2023)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Association of co-exposure to metal(loid)s during pregnancy with birth outcomes in the Tibetan plateau - Lei Zhao; Tiemei Li; Haijing Wang; Yue-Mei Fan; Yuancan Xiao; Xuejun Wang; Shulin Wang; Pin Sun; Pinhua Wang; Zhaxi Jiangcuo; Li Tong; Liehong Wang; et al. (Chemosphere, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Polymeric PDI-based photocatalytic nanoarchitectures promoting the performance of thin film composite membrane for forward osmosis water purification - Pin Zhao; Yang Hu; Xiaoqiang An; Rong Ji; Hao Liu; Hui Zhao; Weilong Song; Yuming Dong; Xinhua Wang (Chemical Engineering Journal, 2023)

Integrating anaerobic acidification with two-stage forward osmosis concentration for simultaneously recovering organic matter, nitrogen and phosphorus from municipal wastewater - Siyi Chen; Zunaira Habib; Zhiwei Wang; Pin Zhao; Weilong Song; Xinhua Wang (Water Research, 2023)

Metal ion assistant transformation strategy to synthesize catechol-based metal–organic frameworks from Ti3C2T precursors - Weikang Wang; Yan Bai; Pin Yang; Shuai Yuan; Feiyang Li; Weiwei Zhao; Beibei Jin; Xuan Zhang; Shujuan Liu; Daqiang Yuan; Qiang Zhao (Science Bulletin, 2023)

TAT-PEP Alleviated Cognitive Impairment by Alleviating Neuronal Mitochondria Damage and Apoptosis After Cerebral Ischemic Reperfusion Injury - Pin Zhao; Jiapo Zhang; JianKe Kuai; Liya Li; Xuying Li; Namin Feng; Hailiang Du; Chen Li; Qiang Wang; Bin Deng (Molecular Neurobiology, 2023)
Paired immunoglobulin-like receptor B (PirB) was identified as a myelin-associated inhibitory protein (MAIP) receptor that plays a critical role in axonal regeneration, synaptic plasticity and neuronal survival after stroke. In our previous study, a transactivator of transcription-PirB extracellular peptide (TAT-PEP) was generated that can block the interactions between MAIs and PirB. We found that TAT-PEP treatment improved axonal regeneration, CST projection and long-term neurobehavioural recovery after stroke through its effects on PirB-mediated downstream signalling. However, the effect of TAT-PEP on the recovery of cognitive function and the survival of neurons also needs to be investigated. In this study, we investigated whether pirb RNAi could alleviate neuronal injury by inhibiting the expression of PirB following exposure to oxygen–glucose deprivation (OGD) in vitro. In addition, TAT-PEP treatment attenuated the volume of the brain infarct and promoted the recovery of neurobehavioural function and cognitive function. This study also found that TAT-PEP exerts neuroprotection by reducing neuronal degeneration and apoptosis after ischemia–reperfusion injury. In addition, TAT-PEP improved neuron survival and reduced lactate dehydrogenase (LDH) release in vitro. Results also showed that TAT-PEP reduced malondialdehyde (MDA) levels, increased superoxide dismutase (SOD) activity and reduced reactive oxygen species (ROS) accumulation in OGD-injured neurons. The possible mechanism was that TAT-PEP could contribute to the damage of neuronal mitochondria and affect the expression of cleaved caspase 3, Bax and Bcl-2. Our results suggest that PirB overexpression in neurons after ischaemic-reperfusion injury induces neuronal mitochondrial damage, oxidative stress and apoptosis. This study also suggests that TAT-PEP may be a potent neuroprotectant with therapeutic potential for stroke by reducing neuronal oxidative stress, mitochondrial damage, degeneration and apoptosis in ischemic stroke.

A novel type of Brassica napus with higher stearic acid in seeds developed through genome editing of BnaSAD2 family - Huibin Huang; Sunny Ahmar; Rana Abdul Samad; Pin Qin; Tong Yan; Qin Zhao; Kabin Xie; Chunyu Zhang; Chuchuan Fan; Yongming Zhou (Theoretical and Applied Genetics, 2023)

Cell activity manipulation through optimizing piezoelectricity and polarization of diphenylalanine peptide nanotube-based nanocomposite - Huiling Guo; Dong-Min Lee; Pin Zhao; So-Hee Kim; Inah Hyun; Byung-Joon Park; Ju-Hyuck Lee; Huajun Sun; Sang-Woo Kim (Chemical Engineering Journal, 2023)

Cytotoxic triterpenoids from the roots of Bupleurum scorzonerifolium - Dan-Qi Li; Zi-Wei Zhao; Fan Jiang; Da Liu; Xiao-Jing Wu; Xue-Gui Liu; Pin-Yi Gao (Phytochemistry Letters, 2023)

Occurrence, spatial distribution, and sources of PFASs in the water and sediment from lakes in the Tibetan Plateau - Yu Chen; Lijia Wei; Wei Luo; Ning Jiang; Yali Shi; Pin Zhao; Bila Ga; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang (Journal of Hazardous Materials, 2023)

Introduction of poly(acrylic acid) sodium into traditional draw solution to enhance its driving capacity in forward osmosis process - Pin Zhao; Ruiping Liu; Huijuan Liu; Jianfeng Peng; Jiuhui Qu (Environmental Science and Pollution Research, 2022)

CDK1 promotes the proliferation of melanocytes in Rex rabbits - Yingying Dai; Shuaishuai Hu; Shaocheng Bai; Jiali Li; Naisu Yang; Pin Zhai; Bohao Zhao; Yang Chen; Xinsheng Wu (Genes & Genomics, 2022)

Superior degradation of phenolic contaminants in different water matrices via non-radical Fenton-like mechanism mediated by surface-disordered WO3 - Ai-Yong Zhang; Shuo Xu; Jing-Wei Feng; Pin-Cheng Zhao; Heng Liang (Environmental Science and Pollution Research, 2022)

Steroid Receptor Coactivator 3 Regulates Synaptic Plasticity and Hippocampus-dependent Memory - Hai-Long Zhang; Bing Zhao; Pin Yang; Yin-Quan Du; Wei Han; Jianming Xu; Dong-Min Yin (Neuroscience Bulletin, 2021)
Steroid hormones play important roles in brain development and function. The signaling of steroid hormones depends on the interaction between steroid receptors and their coactivators. Although the function of steroid receptor coactivators has been extensively studied in other tissues, their functions in the central nervous system are less well investigated. In this study, we addressed the function of steroid receptor coactivator 3 (SRC3) – a member of the p160 SRC protein family that is expressed predominantly in the hippocampus. While hippocampal development was not altered in Src3 +/− mice, hippocampus-dependent functions such as short-term memory and spatial memory were impaired. We further demonstrated that the deficient learning and memory in Src3 +/− mice was strongly associated with the impairment of long-term potentiation (LTP) at Schaffer Collateral-CA1 synapses. Mechanistic studies indicated that Src3 +/− mutation altered the composition of N-methyl-D-aspartate receptor subunits in the postsynaptic densities of hippocampal neurons. Finally, we showed that SRC3 regulated synaptic plasticity and learning mainly dependent on its lysine acetyltransferase activity. Taken together, these results reveal previously unknown functions of SRC3 in the hippocampus and thus may provide insight into how steroid hormones regulate brain function.

Five polyketides isolated from the marine-derived fungus Arthrinium Sp. - Zhaihai Zhao; Wanjing Ding; Pin-Mei Wang; Daoqiong Zheng; Jinzhong Xu (Natural Product Research, 2021)

Formation of persistent free radicals in sludge biochar by hydrothermal carbonization - Zheng Tang; Song Zhao; Yajie Qian; Hanzhong Jia; Pin Gao; Yanming Kang; Eric Lichtfouse (Environmental Chemistry Letters, 2021)

Pathogenic characterization of Aeromonas salmonicida subsp. masoucida turbot isolate from China - Ping Wang; Jie Li; Tian Tian He; Nan Li; Zhao Lan Mo; Pin Nie; Hai Xia Xie (Journal of Fish Diseases, 2020)
Aeromonas salmonicida is a gram‐negative bacterium that is the causative agent of furunculosis. An A. salmonicida strain was isolated from diseased turbot ( Scophthalmus maximus ) with the sign of furunculosis from North China. Based on vapA gene, the strain was further classified as A. salmonicida subsp. masoucida RZ6S‐1. Culturing RZ6S‐1 strain at high temperature (28°C) obtained the virulence attenuated strain RZ6S. Genome sequence comparison between the two strains revealed the loss of the type IV secretion system (T4SS) and type III secretion system (T3SS) from the native plasmid pAsmB‐1 and pAsmC‐1 of wild‐type strain RZ6S‐1, respectively. Further study demonstrated that the wild‐type strain RZ6S‐1, but not its derivative mutant RZ6S, can stimulate apoptosis. Elevated protein level of cleaved caspase‐3 was detected from epithelioma papulosum cyprinid (EPC) cells infected with wild‐type strain RZ6S‐1 as compared with that infected with RZ6S strain. Meanwhile, the invasion of the mutant strain RZ6S was about 17‐fold higher than the wild‐type strain RZ6S‐1, suggesting that some protein(s) from A. salmonicida subsp. masoucida RZ6S‐1 suppress its invasion. The RZ6S mutant strain was attenuated, since its LD 50 is over 10,000 times higher compared to the wild‐type strain as revealed in the turbot infection model.

Preliminary studies of hair follicle regeneration by injections of epidermal stem cells and dermal papilla cells into nude mice - Mingsheng Zhang; Yan Ye; Pin Zhao; Liming Bai; Xinping Li (Cell and Tissue Banking, 2020)
The ultimate goal of organ regenerative therapy is to reproduce fully functional organs to replace which have been damaged as a result of diseases or injury. Although several studies claimed that using different types of cells in some animal models promote hair follicles regeneration, more researches can be done to develop a sufficient and efficient protocol to induce hair generation from different animal models. In this study, we investigated the therapeutic potentials for hair follicle formation by injecting a mixture of epidermal stem cells and dermal papilla cells. Those cells were isolated and culture-expanded. Then we randomly allocated 8 nude mice into two groups. The experiment group received an injection of a mixture that containing of epidermal stem cells and dermal papilla cells. The control group received injection of keratinocyte serum-free medium. The hair follicles regeneration was observed and the injection area was harvested for HE staining. 14 day later, the regenerated hair shafts were observed and HE staining indicated that the newly hair follicle formed the correct structures in experiment group. Furthermore, the mixture injection induced a regular and multilayered stratified epidermis and the epidermis contained of hair follicle-likes structures. Our data showed that injection of a mixture of epidermal stem cells and dermal papilla cells could induce hair follicles regeneration and well-ordered epidermis formation. This study emphasized that the rearrangement of the interactions during seed cells and the niches of the seed cells is essential and necessary for tissue-engineered construct success.

Non-radical activation of H2O2 by surface-disordered WO3 for efficient and selective pollutant degradation with weak matrix effects - Ai-Yong Zhang; Pin-Cheng Zhao; Yuan-Yi He; Yang Zhou; Jing-Wei Feng (Environmental Science and Pollution Research, 2020)

Correction to: Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

The application of forward osmosis for simulated surface water treatment by using trisodium citrate as draw solute - Shihui Yang; Baoyu Gao; Pin Zhao; Chen Wang; Xue Shen; Qinyan Yue; Ho kyong Shon (Environmental Science and Pollution Research, 2019)

Analyzing gravity anomaly variations before the 2016 Ms 6.4 earthquake in Menyuan, Qinghai with an interpolation/cutting potential field separation technique - Jin-Zhao Liu; Tong-Qing Wang; Zhao-Hui Chen; Pin Zhang; Chuan-Dong Zhu; Shuang-Xi Zhang (Applied Geophysics, 2018)

Rice yield development and the shrinking yield gaps in China, 1981–2008 - Yi Chen; Pin Wang; Zhao Zhang; Fulu Tao; Xing Wei (Regional Environmental Change, 2017)

Future extreme temperature and its impact on rice yield in China - Zhao Zhang; Yi Chen; Chenzhi Wang; Pin Wang; Fulu Tao (International Journal of Climatology, 2017)
Rice in China is increasingly suffered from extreme temperature stress ( ETS ) with ongoing climate change. It is projected that ETS would increase notably across the world in the future. However, the spatio‐temporal change of ETS in main rice planting areas in China is still unclear; and the future yield loss caused by ETS ( YL ETS ) has seldom been investigated quantitatively. In this study, we first investigated the spatio‐temporal change of ETS across China under 20 climate change scenarios consisting of five global climate models and four Representative Carbon Pathways (2.6, 4.5, 6.0, and 8.5). Then, using a process‐based crop model ( MCWLA ‐Rice), its 30 sets of model parameters and the 20 climate change scenarios, we conducted a super‐ensemble assessment to investigate the YL ETS over 2020–2049, relative to the baseline period (1980–2009), across China. The results showed that, an increased heat ETS and a decreased cold ETS would be expected for most areas. As a result, a large spatial variability of yield loss would be expected in the future, including severely cold stress for region I (northeastern China, single rice) and region IV (southern China, early rice), but severely heat stress for region III (the middle and lower reaches of Yangtze River, single rice) and region IV (southern China, late rice). Comparing yield loss from both ETS , a decreased change in yield loss would be mainly expected in region I (northeastern China, single rice), while an increased change for region III (the middle and lower reaches of Yangtze River, single rice) and IV (southern China, late rice), with less change for region II (southwestern China, single rice) and IV (southern China, early rice). Finally, some adaptation measures were proposed for the ETS ‐sensitive areas. Our findings are useful to develop effective policies to cope with climate risk and relieve ETS disasters.

Seasonal modeling of hand, foot, and mouth disease as a function of meteorological variations in Chongqing, China - Pin Wang; Han Zhao; Fangxin You; Hailong Zhou; William B. Goggins (International Journal of Biometeorology, 2017)

Comparison of two modified coal ash ferric-carbon micro-electrolysis ceramic media for pretreatment of tetracycline wastewater - Kunlun Yang; Yang Jin; Qinyan Yue; Pin Zhao; Yuan Gao; Suqing Wu; Baoyu Gao (Environmental Science and Pollution Research, 2017)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Recent patterns of production for the main cereal grains: implications for food security in China - Xing Wei; Zhao Zhang; Pin Wang; Fulu Tao (Regional Environmental Change, 2017)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Contribution of aboveground litter to soil respiration in Populus davidiana Dode plantations at different stand ages - Xin Zhao; Fa-dong Li; Wan-jun Zhang; Zhi-pin Ai (Journal of Mountain Science, 2016)

How much yield loss has been caused by extreme temperature stress to the irrigated rice production in China? - Pin Wang; Zhao Zhang; Yi Chen; Xing Wei; Boyan Feng; Fulu Tao (Climatic Change, 2016)

Dynamic variability of the heading–flowering stages of single rice in China based on field observations and NDVI estimations - Zhao Zhang; Xiao Song; Yi Chen; Pin Wang; Xing Wei; Fulu Tao (International Journal of Biometeorology, 2015)

The spatio-temporal variations of surface water quality in China during the “Eleventh Five-Year Plan” - Jingbo Sun; Yi Chen; Zhao Zhang; Pin Wang; Xiao Song; Xing Wei; Boyan Feng (Environmental Monitoring and Assessment, 2015)

A novel SMAD family protein, SMAD9 is involved in follicular initiation and changes egg yield of geese via synonymous mutations in exon1 and intron2 - Jun Xu; Jun Li; Haosen Wang; Guanglin Wang; Jie Chen; Pin Huang; Jienan Cheng; Lu Gan; Zhao Wang; Yafei Cai (Molecular Biology Reports, 2015)

Predictive value of circulating miR-328 and miR-134 for acute myocardial infarction - Fucheng He; Pin Lv; Xue Zhao; Xi Wang; Xuehan Ma; Weiwei Meng; Xianchun Meng; Shuling Dong (Molecular and Cellular Biochemistry, 2014)

Increased topsoil carbon stock across China's forests - Yuanhe Yang; Pin Li; Jinzhi Ding; Xia Zhao; Wenhong Ma; Chengjun Ji; Jingyun Fang (Global Change Biology, 2014)
Biomass carbon accumulation in forest ecosystems is a widespread phenomenon at both regional and global scales. However, as coupled carbon–climate models predicted, a positive feedback could be triggered if accelerated soil carbon decomposition offsets enhanced vegetation growth under a warming climate. It is thus crucial to reveal whether and how soil carbon stock in forest ecosystems has changed over recent decades. However, large‐scale changes in soil carbon stock across forest ecosystems have not yet been carefully examined at both regional and global scales, which have been widely perceived as a big bottleneck in untangling carbon–climate feedback. Using newly developed database and sophisticated data mining approach, here we evaluated temporal changes in topsoil carbon stock across major forest ecosystem in China and analysed potential drivers in soil carbon dynamics over broad geographical scale. Our results indicated that topsoil carbon stock increased significantly within all of five major forest types during the period of 1980s–2000s, with an overall rate of 20.0 g C m −2 yr −1 (95% confidence interval, 14.1–25.5). The magnitude of soil carbon accumulation across coniferous forests and coniferous/broadleaved mixed forests exhibited meaningful increases with both mean annual temperature and precipitation. Moreover, soil carbon dynamics across these forest ecosystems were positively associated with clay content, with a larger amount of SOC accumulation occurring in fine‐textured soils. In contrast, changes in soil carbon stock across broadleaved forests were insensitive to either climatic or edaphic variables. Overall, these results suggest that soil carbon accumulation does not counteract vegetation carbon sequestration across China's forest ecosystems. The combination of soil carbon accumulation and vegetation carbon sequestration triggers a negative feedback to climate warming, rather than a positive feedback predicted by coupled carbon–climate models.

Temperature variations and rice yields in China: historical contributions and future trends - Pin Wang; Zhao Zhang; Xiao Song; Yi Chen; Xing Wei; Peijun Shi; Fulu Tao (Climatic Change, 2014)

Spatial pattern and decadal change of agro-meteorological disasters in the main wheat production area of China during 1991–2009 - Zhao Zhang; Pin Wang; Yi Chen; Shuai Zhang; Fulu Tao; Xiaofei Liu (Journal of Geographical Sciences, 2014)

Spatial and temporal changes of agro-meteorological disasters affecting maize production in China since 1990 - Zhao Zhang; Yi Chen; Pin Wang; Shuai Zhang; Fulu Tao; Xiaofei Liu (Natural Hazards, 2014)

The heat deficit index depicts the responses of rice yield to climate change in the northeastern three provinces of China - Zhao Zhang; Xiaofei Liu; Pin Wang; Jiabing Shuai; Yi Chen; Xiao Song; Fulu Tao (Regional Environmental Change, 2014)

Spatiotemporal changes of global extreme temperature events (ETEs) since 1981 and the meteorological causes - Xiao Song; Zhao Zhang; Yi Chen; Pin Wang; Ming Xiang; Peijun Shi; Fulu Tao (Natural Hazards, 2014)

MicroRNA-124 (miR-124) Regulates Ku70 Expression and is Correlated with Neuronal Death Induced by Ischemia/Reperfusion - Fei Zhu; Jing-Li Liu; Jing-Pin Li; Fang Xiao; Zhao-Xia Zhang; Lei Zhang (Journal of Molecular Neuroscience, 2014)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Increasing concentrations of aerosols offset the benefits of climate warming on rice yields during 1980–2008 in Jiangsu Province, China - Jiabing Shuai; Zhao Zhang; Xiaofei Liu; Yi Chen; Pin Wang; Peijun Shi (Regional Environmental Change, 2013)

Impact of chilling injury and global warming on rice yield in Heilongjiang Province - Xiaofei Liu; Zhao Zhang; Jiabing Shuai; Pin Wang; Wenjiao Shi; Fulu Tao; Yi Chen (Journal of Geographical Sciences, 2013)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Risk assessment of inhalation exposure to polycyclic aromatic hydrocarbons in Taiwanese workers at night markets - Ping Zhao; Kuo-Pin Yu; Chi-Chi Lin (International Archives of Occupational and Environmental Health, 2011)

Hydrogenation properties of mechanically milled Mg2Ni0.8Cr0.2-CoO/Al2O3 composites - Xiu-li Wang; Jiang-ping Tu; Chang-pin Chen; Xiao-bin Zhang; Xin-bing Zhao (Journal of Zhejiang University-SCIENCE B, 2005)